ANALISIS PENJUALAN BERSIH DAN BEBAN OPERASI TERHADAP LABA USAHA PADA PERUSAHAAN DAGANG DI BURSA EFEK INDONESIA - Aisyah; E Janrosl, Viola Syukrina (LPPM Universitas Putera Batam, 2022)
This study aims to further analyze the effect of net sales and operating expenses on operating profit, either partially or simultaneously in trading companies listed on the Indonesia Stock Exchange, wholesale sub-sector.There is a discrepancy between theory and facts that occurs in the company's income statement, the fact is that net sales have increased but operating profit has decreased, and operating expenses have decreased but profits have decreased. Meanwhile, based on the theory, if the sales are higher, the profits will increase, and if the entity can reduce operating expenses, the entity will earn a larger profit.This research is a type of quantitative research, the sampling method used in this study is purposive sampling, with data collection techniques using secondary data taken from the company's financial statements from 2016 - 2020 on the Indonesia Stock Exchange website, with a population of 41 companies and a sample of 10 companies. The results of this study indicate that partially the net sales variable (X1) has a significant effect on operating income (Y), and partially operating expenses (X2) has no significant effect on operating income (Y), simultaneously the variables of net sales and operating expenses significant effect on operating profit variable.